ANALISA PENGARUH RASIO KEUANGAN TERHADAP DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN SUB SEKTOR BATUBARA - Aji, Mareta Danar Purwito; Putra, Brian Qaedi Laksono; Soeroto, Wisudanto Mas (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The energy sector is an attractive sector in the Indonesian capital market. The total market capitalisation of the energy sector IDR 1,162 Trillion or around 10% of the total capitalisation of the Indonesian capital market. The energy sector has several issuers that focus on the coal mining industry. Some coal industry issuers in Indonesia have very good fundamentals and often distribute dividends to their shareholders. The purpose of this study is to determine the effect of financial ratios represented by Current Ratio (CR), Return On Equity (ROE), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) on Dividend Payout Ratio (DPR). This type of research is explanatory research. The population of this study is coal subsector companies that consistently pay dividends from 2021 - 2023. There are 7 company samples that have met certain adjusted criteria. The analysis method in this research is multiple linear regression. The results of the analysis of this study are four independent variables represented by Current Ratio (CR), Return On Equity (ROE), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) simultaneously affect the Dividend Payout Ratio (DPR). While partially only the ROE variable has a significant effect on the Dividend Payout Ratio (DPR).